Teaching-learning strategies for the development of core competencies in secondary education: a reflection from praxeology (Revista Innova Educación, 2023)
The present discussion was considered in light of the changes being incorporated into the curriculum design, specifically within the Dominican educational system. Therefore, the objective was to identify teaching-learning strategies for the development of fundamental competencies in secondary education students, with a reflection from the perspective of praxeology. The theoretical contributions of the Ministry of Education of the Dominican Republic (2016, 2022), Tobón (2008, 2013, 2014, 2018), among others, were assumed. The study was conducted with a positivist paradigm, a quantitative approach, descriptive research, a non-experimental design, and a cross-sectional field study. The population consisted of 36 teachers selected through non-probabilistic accidental sampling from various institutions in Santo Domingo. Data collection was done through a survey with a 30-item questionnaire offering three response options. The questionnaire was validated by five experts, and its reliability was determined using Cronbach's Alpha. The statistical analysis was presented in tables. The findings indicate that secondary-level teachers agree with the application of pre-instructional, co-instructional, and post-instructional strategies for each phase of the pedagogical practice. They utilize problem-based learning, project-based learning, collaborative learning, among others, to develop fundamental competencies. Teachers value these strategies in general, considering them important for the education of students at this level, as outlined in the Dominican curriculum.
Keywords: strategies; teaching; learning; core competencies; secondary level